2014
DOI: 10.1097/mcp.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana and lung diseases

Abstract: There is unequivocal evidence that habitual or regular marijuana smoking is not harmless. A caution against regular heavy marijuana usage is prudent. The medicinal use of marijuana is likely not harmful to lungs in low cumulative doses, but the dose limit needs to be defined. Recreational use is not the same as medicinal use and should be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 47 publications
0
51
0
4
Order By: Relevance
“…35,36 We found no evidence of variation in alcohol use risk across medical conditions, but some evidence of condition-varying risk for marijuana use, which was least prevalent among youth with asthma and cystic fibrosis, as might be expected given the exacerbating effects of smoking on respiratory function. 37,38 Marijuana use also was relatively low among youth with arthritis. Confirming and understanding condition-varying risks for marijuana use is important to understanding outcomes and merits additional investigation; marijuana use may ameliorate symptoms for some conditions, confounding treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 We found no evidence of variation in alcohol use risk across medical conditions, but some evidence of condition-varying risk for marijuana use, which was least prevalent among youth with asthma and cystic fibrosis, as might be expected given the exacerbating effects of smoking on respiratory function. 37,38 Marijuana use also was relatively low among youth with arthritis. Confirming and understanding condition-varying risks for marijuana use is important to understanding outcomes and merits additional investigation; marijuana use may ameliorate symptoms for some conditions, confounding treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 Physical effects on coordination and reaction time raise serious concerns about the contribution of marijuana intoxication to motor vehicle injuries and deaths. 81,82 Medical consequences include respiratory effects 83 and the long-term effects of exposure to carcinogenic components of marijuana smoke, with a recent study from New Zealand finding elevated rates of lung cancer in adults with histories of long-term marijuana smoking. 84 Studies have also shown connections between chronic marijuana use and mental health disorders such as anxiety and schizophrenia.…”
Section: Arguments For and Against Legalization Or Decriminalization mentioning
confidence: 99%
“…35,36 We found no evidence of variation in alcohol use risk across medical conditions, but some evidence of condition-varying risk for marijuana use, which was least prevalent among youth with asthma and cystic fibrosis, as might be expected given the exacerbating effects of smoking on respiratory function. 37,38 Marijuana use also was relatively low among youth with arthritis. Confirming and understanding condition-varying risks for marijuana use is important to understanding outcomes and merits additional investigation; marijuana use may ameliorate symptoms for some conditions, confounding treatment effects.…”
Section: Discussionmentioning
confidence: 99%